2012
DOI: 10.1007/s11103-012-9975-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of superoxide production by Arabidopsis thaliana aldehyde oxidases AAO1 and AAO3

Abstract: Plant aldehyde oxidases (AOs) have gained great attention during the last years as they catalyze the last step in the biosynthesis of the phytohormone abscisic acid by oxidation of abscisic aldehyde. Furthermore, oxidation of indole-3-acetaldehyde by AOs is likely to represent one route to produce another phytohormone, indole-3-acetic acid, and thus, AOs play important roles in many aspects of plant growth and development. In the present work we demonstrate that heterologously expressed AAO1 and AAO3, two prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Possibly, cyanide released by CYP71B6 and other enzymes catalyzing the same reaction is recycled efficiently into central metabolism. As both cytochrome P450s as well as AAO1 (Zarepour et al, 2012) are inhibited by cyanide, rapid removal of this by-product is necessary to prevent shutdown of the biosynthetic pathway. Recently, it was demonstrated that low amounts of cyanide (approximately 0.08 nmol g 21 fresh weight) accumulate in response to Botrytis cinerea infection (García et al, 2013).…”
Section: Discussion Proposed Biosynthetic Pathways Of Icho-derived Sementioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, cyanide released by CYP71B6 and other enzymes catalyzing the same reaction is recycled efficiently into central metabolism. As both cytochrome P450s as well as AAO1 (Zarepour et al, 2012) are inhibited by cyanide, rapid removal of this by-product is necessary to prevent shutdown of the biosynthetic pathway. Recently, it was demonstrated that low amounts of cyanide (approximately 0.08 nmol g 21 fresh weight) accumulate in response to Botrytis cinerea infection (García et al, 2013).…”
Section: Discussion Proposed Biosynthetic Pathways Of Icho-derived Sementioning
confidence: 99%
“…ARABIDOPSIS ALDEHYDE OXIDASE3 (AAO3) catalyzes the last step in abscisic acid biosynthesis , and AAO4 is responsible for benzaldehyde oxidation in siliques (Ibdah et al, 2009). AAO1 and AAO2 as homodimers and heterodimers have a rather broad substrate specificity in vitro (Akaba et al, 1999;Koiwai et al, 2000), and AAO1 was recently shown to catalyze the NADH-dependent production of superoxide anions (Zarepour et al, 2012). It was proposed that aldehyde oxidases are involved in auxin biosynthesis (Seo et al, 1998), and one substrate of the AAO1 homomer is indole-3-acetaldehyde (IAAld), which is oxidized to indole-3-acetic acid (IAA) with an apparent K m value of 39 mM .…”
mentioning
confidence: 99%
“…S8 (Zarepour et al, 2012), we wished to examine whether AAO4 was capable of the same. Additionally, the suitability of various kinds of aldehydes for the generation of ROS by AAO4 was examined, employing aliphatic and aromatic aldehydes after protein fractionation using in-gel assays for O 2 2 -and H 2 O 2 -dependent activity band generation (Sagi and Fluhr, 2001;Yesbergenova et al, 2005).…”
Section: Aao4 Activity With Various Aldehyde Substratesmentioning
confidence: 99%
“…Additionally, Ibdah et al (2009), in their AAO4 activity assay, employed NAD + as a cosubstrate together with the aldehyde substrate. However, the use of NAD + by plants, or for that matter by any eukaryotic AO, is not known (Nishino and Nishino, 1989;Terao et al, 1998;Garattini et al, 2009;Kundu et al, 2012;Zarepour et al, 2012;Li et al, 2014). Moreover, Coelho et al (2012) recently demonstrated that the lack of residues leading to a flexible loop around the FAD domain in mammalian AO crystal structure can account for the fact that AOs are pure oxidases and cannot use NAD + as the final acceptor of reducing equivalents.…”
Section: The Response Of Aao4 Siliques To Various Kinds Of Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation